The relationship between the readability index of the form four English language textbook and the reading level of secondary four students in Johor / Nadzrah Sa'adan - Sa'adan, Nadzrah (2014)
Secondary school acts as a platform in preparing students for tertiary education. A lot of readings in English are required once they enter tertiary education as most of the reading materials are written in English language. Therefore, it is crucial for the secondary teachers to make sure the reading materials used will be able to improve students' reading skills. This study investigated the readability level of Form Four English textbook used in Malaysian schools and its relationship with students' reading level. Utilizing a descriptive correlational research design, 178 Form four students (16 years of age) from Science and Arts stream students from three different schools were chosen by using simple-random sampling technique. Two instruments namely Flesch Reading Ease Formula and Cloze test were used. The Flesch Reading Ease Formula indicated that the textbook is at standard difficulty (appropriate for readers aged 13 to 14 years old), which is below the reading age of the targeted readers. The findings also revealed that majority of the students (45.5%) read the textbook at frustration reading level indicating that the materials that are too difficult for the reader, followed with instructional level that indicates materials are appropriate for students but need teachers' support and guidance (30.9%) and independent level indicates that the materials are too easy for the readers (15.2%). However, no significant relationship was found between gender and students' reading level. It is suggested that text materials to be presented to these students should be suitable with students' reading level and able to provide optimal challenge to the readers.